2001
DOI: 10.1029/2001jb000346
|View full text |Cite
|
Sign up to set email alerts
|

Upper mantle anisotropy from long‐period P polarization

Abstract: Abstract. We introduce a method to infer upper mantle azimuthal anisotropy from the polarization, i.e., the direction of particle motion, of teleseismic longperiod P onsets. The horizontal polarization of the initial P particle motion can deviate by •10 ø from the great circle azimuth from station to source despite a high degree of linearity of motion. Recent global isotropic three-dimensional mantle models predict effects that are an order of magnitude smaller than our observations. Stations within regional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 56 publications
6
56
3
1
Order By: Relevance
“…The 40 broadband stations consist of several different types of seismometers. It often may not be properly appreciated, but just as stations frequently have misoriented horizontal components [Schulte-Pelkum et al, 2001], they also commonly have misreported or miscalibrated response functions. In every study we have performed to date that has involved multiple instrument types (MELT Experiment, northeastern United States/MOMA, Colorado/Rocky Mountain Front, Tanzania), we have found that the instrument response parameters reported for at least one of the instrument types has been incorrect.…”
Section: Appendix A: Corrections For Station Instrumental Responses Amentioning
confidence: 99%
See 1 more Smart Citation
“…The 40 broadband stations consist of several different types of seismometers. It often may not be properly appreciated, but just as stations frequently have misoriented horizontal components [Schulte-Pelkum et al, 2001], they also commonly have misreported or miscalibrated response functions. In every study we have performed to date that has involved multiple instrument types (MELT Experiment, northeastern United States/MOMA, Colorado/Rocky Mountain Front, Tanzania), we have found that the instrument response parameters reported for at least one of the instrument types has been incorrect.…”
Section: Appendix A: Corrections For Station Instrumental Responses Amentioning
confidence: 99%
“…Assuming 4% anisotropy for upper mantle materials, Polet and Kanamori [2002] estimated an anisotropic layer about 100-200 km thick, according to the range of delay times. Combining information from P wave polarization [Schulte-Pelkum et al, 2001], Pn times [Hearn, 1996], Rayleigh and Love velocities, and SKKS and SKS splitting, Davis [2003] concluded that anisotropy is distributed throughout the upper 200 km of the mantle up to the base of the crust. In our study, the strength of azimuthal anisotropy is $1.7% at periods shorter than 100 s and less than 1% at longer periods.…”
Section: Azimuthal Anisotropymentioning
confidence: 99%
“…Anisotropy with a dipping symmetry axis can produce a pattern identical to that caused by a dipping interface in an isotropic medium. It is difficult to distinguish between a dipping axis of symmetry and a dipping interface for a single station from RFs alone (Savage 1998) or from particle motion alone (Schulte-Pelkum et al 2001). …”
Section: Detailed Modelling Of Rfs and Their Variations At Permanent mentioning
confidence: 99%
“…Significant azimuthal anisotropy has been observed for Pn waves beneath oceans (Hess, 1964) and continents (Smith & Ekström, 1999) as well as for travel time residuals of teleseismic P waves (e.g., Babuška et al, 1998). There are clear observations of polarization anomalies of long period P-waves which have been used to infer upper mantle anisotropy (Schulte-Pelkum et al, 2001), but the biggest wealth of observations comes from SKS-splitting measurements (for a review see e.g., Long & Silver, 2009). Surface waves also exhibit a clear anisotropic behaviour.…”
Section: Anisotropic Velocity Tomographymentioning
confidence: 99%